Government budgeting and expenditure controls : theory and practice - Premchand, A. (Washington, D.C. : International Monetary Fund, 1983)
This book offers a comprehensive review of fiscal policies and their implications for budgeting and expenditure controls. It provides an in-depth discussion of techniques, proceedings, and processes of budgeting with illustrative material drawn from the experiencs of industrial and developing countries.
Includes index.
Includes bibliographical references (p. 501-519)
oif 02/11/15
Loans
Keywords: Budget; Expenditures, Public; Finance, Public